Effect of workdays lost to presumptive malaria on households’ poverty status among food crop farming households in rural South West, Nigeria (2020)
This study examined the influence of Workdays Lost to Presumptive Malaria (WLPM) on poverty status of Food Crop Farming Households (FCFHs) in rural South West, Nigeria. The primary data were collected with well-structured questionnaire administered on 395 FCFHs randomly selected using multistage sampling technique. Data were analysed using descriptive statistics, Foster-Greer-Thorbecke and two stage probit least square regression model at α0.05. The results show that 88.6% of the households were male-headed, age was 56.41 ±9.34 years. Years of schooling and farming experience were 4.80±4.65 and 29.53 ±10.78, respectively. Only 37.2%, 45.1% and 24.6% have access to electricity, extension services and agricultural credit, respectively. The annual farm income was N452,711.70±153,704.70 (equivalent to N37,725.97 per month). In a year, an average of 73.49 workdays (valued at N58,358.5) was lost to presumptive malaria per household. The Mean Per Capita Household Expenditure (MPCHE) per month was N5,605.89, the poverty line (i.e 2/3 of MPCHE) was N3,737.26. FGT model results indicate that poverty incidence, depth and severity were 0.425, 0.031 and 0.004, respectively. The incidence of poverty increased with increased in WLPM. In the 2SPLS analysis, the coefficient of WLPM was positive (β=0.0607) and statistically significant (p-value = 0.049), implies that increase in WLPM increase the probability of households being in poverty. The result of the Wald test of exogeneity suggests that the WLPM is truly endogenous to household poverty status. Therefore, WLPM had an increasing effect on poverty status of the respondents. The study recommended that, poverty interventions should adequately incorporate strategies on malaria prevention and control; and be extended to rural areas as a way of poverty reduction among rural populace. Also, the national health insurance scheme needs to incorporate rural farming households and people in the informal sector to reduce the out-of-pocket spending on malaria treatment as a poverty reduction strategy.